Back Cover: Imaging Glycosylation In Vivo by Metabolic Labeling and Magnetic Resonance Imaging (Angew. Chem. Int. Ed. 4/2016). Issue 4 (14th December 2015) - Neves, André A.; Wainman, Yéléna A.; Wright, Alan; Kettunen, Mikko I.; Rodrigues, Tiago B.; McGuire, Sarah; Hu, De‐En; Bulat, Flaviu; Geninatti Crich, Simonetta; Stöckmann, Henning; Leeper, Finian J.; Brindle, Kevin M.
Abstract : Cell‐surface glycans were imaged in live mice by magnetic resonance imaging, following metabolic labeling with an azido sugar and subsequent bioorthogonal reaction with a strained cyclooctyne linked to a gadolinium contrast agent. In their Communication onpage 1286 ff., A. A. Neves et al. show that significant azido sugar dependent contrast was observed in various tissues two hours after administration of the contrast agent.